Cell-imprinted biomimetic interface for intelligent recognition and efficient capture of CTCs. (7th August 2019) - Gao, Su; Chen, Shuangshuang; Lu, Qinghua
Abstract : Synergistically contributing to plastic and natural antibodies, a cell-imprinted biomimetic interface exhibited high sensitivity and efficiency in CTC capture, providing novel insight into cell–biointerface interactions. Abstract : The efficient recognition and isolation of rare cancer cells from blood has great significance for early cancer diagnosis and monitoring prognosis. In this paper, we propose a cell-imprinted biomimetic interface for highly efficient capture of circulating tumor cells (CTCs) through the use of target cells as an imprint template. The cell-morphology topologies and residual biomolecular receptors on the cell-imprinted interface recognize template cells by mimicking the specific immunoaffinity of the antibody–antigen (known as plastic antibody). Furthermore, we introduced a natural antibody (anti-EpCAM) to accelerate the CTC–material interaction. Due to the synergistic contribution of natural and plastic antibodies, the imprinted surface exhibited high performances in CTC detection on an artificial blood sample, with a capture efficiency higher than 55%. In addition to the experiment, we conducted a systematic analysis of the biochemical recognition (real antibody anti-EpCAM and plastic receptor) and topographic interaction to gain insight into the cell–biointerface interaction. The results of this study provide new prospects for designing cell–material interaction interfaces for future cell-based biological research and clinical applications.